2004
DOI: 10.1310/6f83-n39q-9ppp-lmvv
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of ProbioticLactobacillus rhamnosusGG on Prolonged, Noninfectious Diarrhea in HIV Patients on Antiretroviral Therapy: A Randomized, Placebo-Controlled, Crossover Study

Abstract: Probiotic LGG preparation was well-tolerated in HIV infected patients. No significant differences in noninfectious diarrhea or gastrointestinal symptoms compared to placebo could be observed in this crossover study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 38 publications
1
66
0
4
Order By: Relevance
“…When treated with L. reuteri SD2112, no safety concerns arose among moderately immune-compromised HIV patients (>350 CD4 + cells/µl) [63]. In another study of severe immune compromised HIV patients (<200 CD4 + cells/µl), no safety concerns were detected with use of L. rhamnosus [129]. To date, five case studies of lactobacillemia have been reported in end-stage AIDS patients.…”
Section: Safetymentioning
confidence: 97%
See 1 more Smart Citation
“…When treated with L. reuteri SD2112, no safety concerns arose among moderately immune-compromised HIV patients (>350 CD4 + cells/µl) [63]. In another study of severe immune compromised HIV patients (<200 CD4 + cells/µl), no safety concerns were detected with use of L. rhamnosus [129]. To date, five case studies of lactobacillemia have been reported in end-stage AIDS patients.…”
Section: Safetymentioning
confidence: 97%
“…A Cochrane review concluded that probiotics are a useful adjunct to lower the occurrence and reduce the length of episodes of infectious diarrhea (reviewed in [127]). Synbiotics (probiotics combined with prebiotics) have also been shown to reduce diarrhea associated with ART use [128] but these findings could not be confirmed by a cross-over study [129]. Although the application of probiotics to prevent gastrointestinal infections and the concomitant inflammatory state among HIV patients bears promise, no studies have so far been conducted to assess its potential.…”
Section: Effects On Intestinal Microbiota and Infectionsmentioning
confidence: 99%
“…Probiotics have been widely used in food processing for many years, and overall have an excellent safety record, as supported by reviews 48,49 . Many small studies also support the safety of particular probiotic strains in particular high risk populations [50][51][52] . But several reports have directly linked cases of Lactobacillus and other bacterial sepsis to the ingestion of probiotic supplements 53 .…”
Section: Safety Of Probioticsmentioning
confidence: 97%
“…Furthermore, probiotics have been shown to upregulate T-regulatory lymphocytes (Baroja et al, 2007;Foligne et al, 2008) potentially skewing the immune system away from a Th-2-dominant state (Mohamadzadeh et al, 2005). Probiotic usage has been shown to be safe among people living with HIV (Wolf et al, 1998;Salminen et al, 2004) and recent randomized trials in Brazil (Trois et al, 2008) and Nigeria (Anukam et al, 2006) suggest that probiotic use can increase the CD4 count. In the Nigerian study, conventional yogurt fermented with Lactobacillus delbruekii var bulgaricus and Streptococcus thermophilus was supplemented with probiotic Lactobacillus rhamnosus GR-1 and L. reuteri RC-14.…”
Section: Some Clinical Evidence Of Probiotics In Helping To Reduce Thmentioning
confidence: 99%